The Influence of Risk Management and Good Corporate Governance (GCG) on Company Performance With Leverage as a Moderating Variable in Consumer Goods Industrial Sector Companies Listed on the IDX for the 2015-2019 Period - Masno Marjohan (Program Pascasarjana Universitas Negeri Makassar, 2021)
ABSTRACTThis study aims to analyze the effect of good corporate governance (GCG), risk management on company performance. The population in this study came from the consumer goods industry sector companies listed on the Indonesia Stock Exchange for the 2015-2019 period. The sampling technique is a purposive sampling method with the secondary data type, which produces a sample of 27 companies. The data analysis method used descriptive statistical analysis and partial least squares (PLS) analysis. The results of this study show how that Risk Management does not affect Company Performance, The results of Good Corporate Governance (GCG) affect the Company's Performance, simultaneously concluded that simultaneously the variables of GCG and Risk Management have a positive and significant effect on variable Y, namely Company Performance and based on the Cross-section F value of 0.6478, the value of Cross-section F probability is greater than the significance level of 0.05 that is 0.6478> 0.05, it can be concluded that H0 is rejected and H1 is accepted which shows positively Leverage Moderates Risk Management on Company Performance and based on the Cross-section F value of 0.0000, the value of Cross-section F probability is smaller than the significance level of 0.05 that is 0.0000 < 0.05, it can be concluded that H0 is rejected and H1 is accepted which shows positively Leverage Moderates Good Corporate Governance on Company Performance.